Multi-objective optimization for the proper selection of the best heat pump technology in a fuel cell-heat pump micro-CHP system - Xiaochao Fan; Hexu Sun; Zhi Yuan; Zheng Li; Ruijing Shi; Navid Razmjooy (Energy Reports, 2020)
In this paper, a new multi-objective technique has been proposed for optimal analysis of three different candidate heat pump solutions including the vapor compression cycle (VCC), trans-critical R744 cycle, and Peltier device to determine which one gives the best configuration and better performance on a hybrid heat pump and fuel cell-based micro-CHP system. Here, a sunflower optimization algorithm is utilized to provide two different objectives: minimizing the combined yearly maintenance and capital costs and maximizing the performance of the hydrogen energy consumption. Simulation results show that using the VCC, according to its efficient and low-cost characteristics for cell stack and lithium battery maintenance, gives the best solution for the presented hybrid system.
Keywords: 330; Fuel cell; Heat pump; Micro CHP; Multi-objective optimization; Sunflower optimization algorithm